An analysis on Islamic social finance for protection and preservation of Maqāṣid al-Sharī‘ah - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah (IIUM Press, 2017)
Islamic social finance is akin to the conventional social finance but the former is subjected to the established principles of Sharī‘ah. In generating positive impacts to the society, the Islamic social finance and its instruments must be utilised in protecting and preserving the Maqāṣid al-Sharī‘ah. A critical analysis on the Islamic social finance in relation to the Maqāṣid al-Sharī‘ah is provided through this research. By using the doctrinal and qualitative methods, the practices of the Islamic social finance as applied in OIC member states are reviewed and provided as examples. Problems of implementation of Islamic social finance in the OIC countries are listed; while tentative solutions are suggested with a hope of triggering better solutions. At the end of discussion, a list of recommendations for future researches is proposed for considerations.